2015
DOI: 10.1093/ndt/gfv054
|View full text |Cite
|
Sign up to set email alerts
|

Familial C3 glomerulonephritis associated with mutations in the gene for complement factor B

Abstract: We report the first case of familial C3 glomerulonephritis (C3GN) associated with mutations in the gene for complement factor B (CFB). A 12-year-old girl was diagnosed with biopsy-proven C3GN. Her mother had a history of treatment for membranoproliferative glomerulonephritis, and her brother had hypocomplementemia without urinary abnormalities. DNA analysis revealed heterozygosity for CFB p.S367R in the patient, mother and brother. Evaluation of the structure-function relationship supports that this mutation h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Although C3Nef is common in DDD, 4 recent studies also have shown C3G associated with abnormalities in CFB, both genetic and acquired. 15 , 16 aCFB is similar to C3Nef, binds and stabilizes C3bBb convertase (solid phase), and prevents decay, resulting in accelerated C3 consumption. 17 , 18 Presence of both C3Nef and aCFB is reported in 9% of patients with C3G.…”
Section: Discussionmentioning
confidence: 99%
“…Although C3Nef is common in DDD, 4 recent studies also have shown C3G associated with abnormalities in CFB, both genetic and acquired. 15 , 16 aCFB is similar to C3Nef, binds and stabilizes C3bBb convertase (solid phase), and prevents decay, resulting in accelerated C3 consumption. 17 , 18 Presence of both C3Nef and aCFB is reported in 9% of patients with C3G.…”
Section: Discussionmentioning
confidence: 99%
“…Complement factors H (CFH) and B (CFB), both integral mediators of the alternative pathway of the immune system, have also been investigated. 59 , 60 The CFH rs800292 (I62V) A allele was negatively associated with DR in a series of 552 Chinese patients with type 2 diabetes ( P =0.04). 61 In the same series, the CFB rs1048709 (R150R) A allele was significantly associated with DR in type 2 diabetes ( P =0.035).…”
Section: Newer Candidate Genesmentioning
confidence: 98%
“…Rare genetic variants in C3 and CFB have also been described in cohorts of C3G and MPGN [ 87 ] [ 66 ] and includes the S367R variant in CFB in one familial case of C3GN [ 95 ]. Most of these variants have not been functionally studied (Table 2 ).…”
Section: C3 Glomerulopathymentioning
confidence: 99%